Improved Quantification of Cardiac Amyloid Burden in Systemic Light Chain Amyloidosis: Redefining Early Disease? - Cuddy, Sarah A M; Bravo, Paco E; Falk, Rodney H; El-Sady, Samir; Kijewski, Marie Foley; Park, Mi-Ae; Ruberg, Frederick L; Sanchorawala, Vaishali; Landau, Heather; Yee, Andrew J; Bianchi, Giada; Di Carli, Marcelo F; et al. (JACC. Cardiovascular imaging, 2020)
The purpose of this study was to determine phenotypes characterizing cardiac involvement in AL amyloidosis by using direct (fluorine-18-labeled florbetapir {[ F]florbetapir} positron emission tomography [PET]/computed tomography) and indirect (echocardiography and cardiac magnetic resonance [CMR]) imaging biomarkers of AL amyloidosis. Cardiac involvement in systemic light chain amyloidosis (AL) is the main determinant of prognosis and, therefore, guides management. The hypothesis of this study was that myocardial AL deposits and expansion of extracellular volume (ECV) could be identified before increases in N-terminal pro-B-type natriuretic peptide or wall thickness. A total of 45 subjects were prospectively enrolled in 3 groups: 25 with active AL amyloidosis with cardiac involvement (active-CA), 10 with active AL amyloidosis without cardiac involvement by conventional criteria (active-non-CA), and 10 with AL amyloidosis with cardiac involvement in remission for at least 1 year (remission-CA). All subjects underwent echocardiography, CMR, and [ F]florbetapir PET/CT to evaluate cardiac amyloid burden. The active-CA group demonstrated the largest myocardial AL amyloid burden, quantified by [ F]florbetapir retention index (RI) 0.110 (interquartile range [IQR]: 0.078 to 0.139) min , and the lowest cardiac function by global longitudinal strain (GLS), median GLS -11% (IQR: -8% to -13%). The remission-CA group had expanded extracellular volume (ECV) and [ F]florbetapir RI of 0.097 (IQR: 0.070 to 0.124 min ), and abnormal GLS despite hematologic remission for >1 year. The active-non-CA cohort had evidence of cardiac amyloid deposition by advanced imaging metrics in 50% of the subjects; cardiac involvement was identified by late gadolinium enhancement in 20%, elevated ECV in 20%, and elevated [ F]florbetapir RI in 50%. Evidence of cardiac amyloid infiltration was found based on direct and indirect imaging biomarkers in subjects without CA by conventional criteria. The findings from [ F]florbetapir PET imaging provided insight into the preclinical disease process and on the basis of interpretation of expanded ECV on CMR and have important implications for future research and clinical management of AL amyloidosis. (Molecular Imaging of Primary Amyloid Cardiomyopathy [MICA]; NCT02641145).